Biological and clinical manifestations of juvenile Huntington's disease: a retrospective analysis. Issue 11 (November 2018) - Fusilli, Caterina; Migliore, Simone; Mazza, Tommaso; Consoli, Federica; De Luca, Alessandro; Barbagallo, Gaetano; Ciammola, Andrea; Gatto, Emilia Mabel; Cesarini, Martin; Etcheverry, Jose Luis; Parisi, Virginia; Al-Oraimi, Musallam; et al.
Summary: Background: Huntington's disease is a rare, neurodegenerative disease caused by an expanded CAG repeat mutation in the huntingtin gene. Compared with adult-onset Huntington's disease, juvenile Huntington's disease (onset ≤20 years) is even rarer and has not been studied extensively. We aimed to further characterise juvenile Huntington's disease by examining the effect of CAG repeat size on disease presentation, progression, and survival. Methods: We did a retrospective analysis of patients with juvenile Huntington's disease aged 20 years or younger, according to the length of their CAG repeat and who had disabling psychiatric symptoms (with motor symptoms) or motor symptoms alone, and of patients with adult-onset Huntington's disease manifesting aged 30–60 years with 40 or more CAG repeats, from the REGISTRY and ENROLL-HD platforms and from two institutional databases (Lega Italiana Ricerca Huntington Foundation and the Instituto Neurociencias de Buenos Aires and the Sanatorio de la Trinidad Mitre). Patients with psychiatric but no motor symptoms were excluded. We compared symptoms at onset and longitudinally in patients with juvenile Huntington's disease with highly expanded (HE subgroup) or low expansion (LE subgroup) mutations, grouped by hierarchical clustering analysis. We also compared disease progression (longitudinal change in Unified Huntington's Disease Rating Scale–Total Motor Score) and survival of patients with juvenile and adult-onset Huntington's disease. Findings: We extracted medical records from 580 patients entered into the studies or databases between June 23, 2004, and March 31, 2018, of whom 36 patients met our definition of juvenile Huntington's disease and 197 for adult-onset Huntington's disease. According to caregiver reports, gait disturbance was more often a first presenting symptom in the HE subgroup (eight [80%] of 10 patients) than in the LE subgroup (seven [27%] of 26 patients; p=0·0071), whereas loss of hand dexterity was more common in the LE subgroup (11 [42%] of 26 patients) than in the HE subgroup (0 [0%] of 10 patients; p=0·0160). Compared with the LE subgroup, development delay (0 [0%] in the LE subgroup vs nine [90%] in the HE subgroup; p<0·0001), severe gait impairment (nine [35%] in the LE subgroup vs nine [90%] in the HE subgroup; p=0·0072), and seizures (three [11%] in the LE subgroup vs eight [80%] in the HE subgroup; p<0·0001) prevailed over time in the HE subgroup. Disease progression was more rapid in juvenile Huntington's disease (n=14) than in adult-onset Huntington's disease (n=52; generalised estimating equation model, p=0·0003). Of 121 deceased patients, median survival was shorter in the juvenile Huntington's disease (n=17) cohort than in adult-onset Huntington's disease (n=104) cohort (hazard ratio 2·18 [95% CI 1·08–4·40]; p=0·002). Interpretation: Patients with HE juvenile Huntington's disease differ clinically from patients with LE juvenile Huntington's disease or adult-onset Huntington's disease, suggesting reclassification of this particularly aggressive form of Huntington's disease might be required. Funding: Lega Italiana Ricerca Huntington Foundation and IRCCS Ospedale Casa Sollievo della Sofferenza.